Implementation of Warm Compress Therapy for Hyperthermia in Patients with Tropical Malaria: A Case Study (PT. LARPA JAYA PUBLISHER, 2025)
Malaria is an infectious disease transmitted by infected female Anopheles mosquitoes. This disease is caused by the parasitic Plasmodium protozoa that enter the human bloodstream through mosquito bites. Among the various types of Plasmodium that can infect humans, Plasmodium knowlesi, Plasmodium vivax, Plasmodium ovale, Plasmodium malariae, and Plasmodium falciparum are the most dangerous because they can cause death or serious complications. This case study aims to evaluate the effect of warm compresses on hyperthermia in tropical malaria patients in class I & II rooms of Serui Regional Hospital, Papua on February 18, 2025. The author uses a descriptive research method by conducting observations and observations using a nursing process approach. The results of the study showed that the application of warm compress therapy to hyperthermia combined with pharmacological therapy was effective in overcoming hyperthermia in tropical malaria patients. There was a decrease in body temperature from 39.8 ? to 36.7 ? after implementation for 1 day. Monitoring vital signs and evaluating body temperature regularly is very important to assess the effective ness of the intervention. Conclusion: This study emphasizes the effect of warm compress as a non-pharmacological approach in the management of hyperthermia in tropical malaria patients to reduce body temperature and prevent further complications.